Activity of the SNARE Protein SNAP29 at the Endoplasmic Reticulum and Golgi Apparatus - Morelli, Elena; Speranza, Elisa A.; Pellegrino, Enrica; Beznoussenko, Galina V.; Carminati, Francesca; Garré, Massimiliano; Mironov, Alexander A.; Onorati, Marco; Vaccari, Thomas (Frontiers in Cell and Developmental Biology, 2021)
Snap29 is a conserved regulator of membrane fusion essential to complete autophagy and to support other cellular processes including cell division. In humans, inactivating SNAP29 mutations cause CEDNIK syndrome, a rare multi-systemic disorder characterized by congenital neuro-cutaneous alterations. Fibroblasts of CEDNIK patients show alterations of the Golgi apparatus (GA). However, whether and how Snap29 acts at the GA is unclear. Here, we investigate SNAP29 function at the GA and Endoplasmic Reticulum (ER). As part of elongated structures in proximity of these membrane compartments, a pool of SNAP29 forms a complex with Syntaxin18, or with Syntaxin5, that we find required to engage SEC22B-loaded vesicles. Consistent with this, in HeLa cells, in neuroepithelial stem cells and in vivo, decreased SNAP29 activity alters GA architecture and reduces ER to GA trafficking. Our data reveal a new regulatory function of Snap29 in promoting secretory trafficking.